Glucose respiration and fermentation in Zygosaccharomyces bailii and Saccharomyces cerevisae express different sensitivity patterns to ethanol and acetic acid - Estevinho, Leticia M. (2011)
In the yeast Zygosaccharomyces bailii ISA 1307, respiration and fermentation of glucose were exponentially inhibited by ethanol, both processes displaying similar sensitivity to the alcohol. Moreover, the degree of inhibition on fermentation was of the same magnitude as that reported for Saccharomyces cerevisiae. Acetic acid also inhibited these two metabolic processes in Z. bailii, with the kinetics of inhibition again being exponential. However, inhibition of fermentation was much less pronounced than in S. cerevisiae. The values estimated with Z. bailii for the minimum inhibitory concentration of acetic acid ranged from 100 to 240 mmol 1(-1) total acetic acid compared with values of near zero reported for S. cerevisiae. The inhibitory effects of acetic acid on Z. bailii were not significantly potentiated by ethanol.